Characterization of alkaline xylanases from Bacillus pumilus - Duarte,Marta Cristina Teixeira (2000)
Alkaline xylanases produced by four different strains of Bacillus pumilus were characterized. The optimal pH and temperature were pH 9.0 and 60ºC for strain 13a, and pH 8.0 and 55ºC for strains 5(2), 5(14), and 4a. Under these conditions the following activities were found after 10 min in the presence of 1% xylan (birchwood): 328 U.ml-1, 131 U.ml-1, 90 U.ml-1, and 167 U.ml-1, respectively, for the four strains. The enzymes were stable at 40ºC, with 40% of the xylanase activity remaining after 2 hours for the enzymes of strain 5(2) and 60% for the other three strains. Stability at 50ºC was improved by addition of glycerol. Taking into account the conditions under which kraft pulps are bleached during the manufacture of paper, xylanases from B. pumilus exhibit favorable potential for application to bleaching in the paper making process.